UPAYA PEMBERDAYAAN EKONOMI MASYARAKAT MELALUI USAHA GRIYA BATIK SENGGURUH KEPANJEN DALAM PERSPEKTIF EKONOMI ISLAM - Nurwakhidah, Ana (LP2M STAI Miftahul 'Ula (STAIM) Nganjuk, 2022)
This study aims to determine and analyze the efforts and stages of community economic empowerment in an Islamic perspective through the Griya Batik business located in Sengguruh Village, Kepanjen District. This study uses descriptive qualitative methods with a research focus on efforts to empower the community's economy, such as from capital, the Griya Batik management system, human resources to be empowered and various batik trainings to improve batik skills. This research was conducted at Griya Batik Sengguruh with the problem of the stages of economic empowerment through the business of Griya Batik Sengguruh in terms of sharia economic law. The results of the study indicate that community empowerment through Griya Batik Sengguruh affects people who are not yet empowered in terms of skills and financially able to reap good results. Griya Batik Sengguruh is also able to empower socially and economically. In practice, the system used at Griya Batik Sengguruh is in accordance with the principles of Sharia Economics.